The Importance of Character for the Generation in the Digital Era - Fivi Setya Lestari (Yayasan Insan Mulia Bima, 2024)
At this time we are entering the digital era or what is usually called the era of globalization. The era of globalization is marked by increasing technological advances that are increasingly fast and sophisticated, making it easier for people to freely access information. This of course has positive and negative impacts. To reduce and minimize the formation of negative behavior as a result of this era, it is important to implement character education for children. In its implementation, it requires participation and cooperation from various elements, including parents, teachers and schools. This research uses source search methods and data construction from various sources such as books, journals and research conducted. Library information obtained from various references is analyzed critically to support proportions and ideas. Data accuracy and adequacy are prioritized, with emphasis on data validity which reflects the suitability between data records and the reality that occurs in the research context. The aim of the research is to understand the phenomenon by gaining an in-depth understanding of the behavior, perceptions, motivations and actions of the study subjects in a holistic manner